2016
DOI: 10.1590/01047760201622042192
|View full text |Cite
|
Sign up to set email alerts
|

Rice Straw/Thermoplastic Composite: Effect of Filler Loading, Polymer Type and Moisture Absorption on the Performance

Abstract: ABSTRAT: Thermoplastic composites made with 45, 60 and 75% of rice straw as filler and two types of thermoplastics, virgin polyethylene (PE) and polypropylene (PP) were evaluated. The final boards were made with and without maleic anhydride modified polypropylene (MAPP) at 2% of the total weight of each specimen. The flexural and tensile strengths were measured for dry composites and also measured after 24 h of water immersion of the composites (wet condition). By increasing the filler content, the flexural an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Therefore, it can be claimed that moisture is not a problem for irradiated HWC composites, under consideration, because the lignocellulosic fillers, post irradiation, may be totally encapsulated into the polymer matrix. In this case, polymers would protect the fibers because they are hydrophobic .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it can be claimed that moisture is not a problem for irradiated HWC composites, under consideration, because the lignocellulosic fillers, post irradiation, may be totally encapsulated into the polymer matrix. In this case, polymers would protect the fibers because they are hydrophobic .…”
Section: Resultsmentioning
confidence: 99%
“…5). This was because these systems had an insufficient amount of matrix to fill in and cover all fibers [24,25]. Generally, the porosity in solid materials is highly related to a decline in their mechanical properties [26][27][28].…”
Section: Effect Of Fiber Volume Fraction On the Composite Propertiesmentioning
confidence: 99%
“…Rice straw & urea formaldehyde 0.62 [8] Rice straw & urea formaldehyde 0.79 [24] Rice straw & polyethylene 0.90 [17] Rice straw & polypropylene 0.88 [17] Rice straw & polypropylene 0.56 [23] Rice straw & epoxy resin (20 mesh of rice straw) 0.48 [16] Rice straw & epoxy resin (60 mesh of rice straw) 0.87 This study…”
Section: Density (G/cm 3 )mentioning
confidence: 99%
“…The previous study conducted by Mohammadi et al indicated that the type of matrix and fiber loading influenced the flexural and tensile strengths of the composite [17]. Besides the matrix, particle size may also affect the physical and mechanical properties of the particleboard [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation